Analyzing Node Density Impact on End-to-End Delay and Throughput in Mobile Ad hoc Network Video Conferencing Services - Kango, Riklan; Jamal, Nurwahidah; Ihsan (Universitas Medan Area, 2024)
Video conferencing services have gained significant popularity in recent years, enabling real-time communication and collaboration among individuals and groups. However, the performance of video conferencing systems over MANETs poses challenges of topology fluctuations and node density. This research paper aims to present an analysis of end-to-end delay and throughput in video conferencing over MANETs. The main objective is to identify the impact of node density in MANETs on video conferencing user experience. To conduct the study, an experimental setup of Zoom cloud meeting service was designed, consisting of a simulated MANET environment and a video conferencing application. End-to-end delay and throughput were measured via Wireshark software based on interconnected node scenarios and different configurations at densities of 2 and 4 nodes. The collected data was analyzed using appropriate statistical techniques to identify trends, patterns. The end-to-end delay analysis results revealed the impact of fluctuating network density conditions, on the overall delay experienced during the video conferencing session increased by 27%. While throughput analysis revealed a 65% decrease in data transfer capacity caused by higher packet loss factor in MANET. The integrated analysis explores the relationship between end-to-end delay and throughput, providing insight into optimization strategies. These findings can guide the design and implementation of more efficient and reliable video conferencing systems in mobile ad-hoc environments, In the face of fluctuations in node density, these findings can encourage the development of QoS mechanisms specifically designed for MANETs. These mechanisms can prioritize video packets and allocate network resources effectively, ensuring better user experience and overcoming resource constraints